Prevalencia de Babesia bovis en bovino, parroquias Canuto y Santa Rita, Chone - Rodríguez Bravo, Dilia Milena (2025)
The study was conducted in the parishes of Canuto and Santa Rita, located in the canton of Chone. This research was quantitative in nature, based on the collection and analysis of numerical data obtained through diagnostic tests applied to biological samples, with the objective of determining the prevalence of Babesia bovis in the studied bovine population. A total of 245 samples were processed in the Chemistry Laboratory of the Veterinary Medicine program at the Escuela Superior Politécnica Agropecuaria de Manabí, using the blood smear and Giemsa staining techniques. Out of these, 94 cattle tested positive, resulting in a prevalence of 38.46% in Canuto, 38.34% in Santa Rita, and an overall prevalence of 38.37%. Based on these findings, it is concluded that there is a need to establish control measures and provide training on the disease and its prevention, with the purpose of developing a prevention and management plan for babesiosis.